Analisis Pengaruh Kualitas Produk, Harga, dan Social Media Marketing terhadap Minat Pembelian (Studi pada Angkringan Djoegjakarto) - Ardiansyah, Rafi; Fitria, Shoimatul (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT Based on the results of existing pre-research, it is known that the sales level at Angkringan Djoegjakarto experienced a drastic decline in April 2023 and there were fluctuations in the sales level in 2023. This study aims to analyze the effect of product quality, price, and social media marketing towards sales level in Angkringan Djoegjakarto. This study places Angkringan Djoegjakarto's social media followers as the research population, then sampling was carried out using purposive sampling. The sample in this study amounted to 100 respondents with the criteria of Angkringan Djoegjakarto consumers in Bogor Regency who are 17 (seventeen) years old, know and follow social media from Angkringan Djoegjakarto, and have bought and visited Angkringan Djoegjakarto at least 1 (one) time within the last 3 (three) months). The collected data were analyzed using multiple linear regression methods and analyzed with SPSS software. The results of this study indicate that product quality has a significant positive effect on the purchase intention of Angkringan Djoegjakarto, price has a significant positive effect on the purchase intention of Angkringan Djoegjakarto, and social media marketing has a significant positive effect on the purchase intention of Angkringan Djoegjakarto